2017
DOI: 10.3390/toxins9120389
|View full text |Cite
|
Sign up to set email alerts
|

Site I Inactivation Impacts Calmodulin Calcium Binding and Activation of Bordetella pertussis Adenylate Cyclase Toxin

Abstract: Site I inactivation of calmodulin (CaM) was used to examine the importance of aspartic acid 22 at position 3 in CaM calcium binding, protein folding, and activation of the Bordetella pertussis adenylate cyclase toxin domain (CyaA-ACD). NMR calcium titration experiments showed that site I in the CaM mutant (D22A) remained largely unperturbed, while sites II, III, and IV exhibited calcium-induced conformational changes similar to wild-type CaM (CaMWt). Circular dichroism analyses revealed that D22A had comparabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Guo and colleagues used biochemical, biophysical, and computational approaches to show that interaction occurs between N-terminal CaM and CyaA-ACD [ 18 ]. Domain flexibility and metal-sensing properties of CaM are affected by CyaA-ACD [ 16 , 19 21 ]. Hydrodynamic changes (which are indicative of changes in global shape [ 15 ]) and long range structural rearrangements [ 19 , 22 ] have been reported in CaM/CyaA-ACD complexes, also pointing to the importance of conformational plasticity in this B .…”
Section: The Role Of Dynamic Conformational Changes In Acts Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Guo and colleagues used biochemical, biophysical, and computational approaches to show that interaction occurs between N-terminal CaM and CyaA-ACD [ 18 ]. Domain flexibility and metal-sensing properties of CaM are affected by CyaA-ACD [ 16 , 19 21 ]. Hydrodynamic changes (which are indicative of changes in global shape [ 15 ]) and long range structural rearrangements [ 19 , 22 ] have been reported in CaM/CyaA-ACD complexes, also pointing to the importance of conformational plasticity in this B .…”
Section: The Role Of Dynamic Conformational Changes In Acts Functionmentioning
confidence: 99%
“…pertussis virulence factor. Targeted mutations reduce conformational stability and activation, providing further evidence that both dynamics and unique structural determinants are crucial regulators controlling CaM-dependent stimulation of CyaA-ACD [ 12 , 16 , 18 , 19 , 21 23 ]. Taken together, these findings imply that conformational switching, particularly in CyaA-ACD, is modulated in part by the formation of stabilizing interactions with CaM and is crucial to enzymatic activation.…”
Section: The Role Of Dynamic Conformational Changes In Acts Functionmentioning
confidence: 99%
“…Recently, we showed that the catalytic domain contains a large region of structural disorder [ 9 ], and is poorly active in the absence of calmodulin, while calmodulin binding induces local folding, leading to the stabilization of the enzymatic core and the production of massive amounts of cAMP at the expense of ATP. Christian Johns and Natosha Finley report that the inactivation of calcium binding at Site 1 of calmodulin affects the stability of the N-terminal region of calmodulin and, consequently, its interaction with the catalytic domain of CyaA [ 10 ]. In the same topic, Thérèse Malliavin used molecular dynamics to highlight the contributions of several regions from both calmodulin and the CyaA catalytic domain to the formation of the active enzymatic complex [ 11 ].…”
mentioning
confidence: 99%